PROTEINS AND SALT SOLUTIONS - Akzamov Valery Bakhridinovich (Galaxy International Interdisciplinary Research Journal, 2021)
As you know, the main way of penetration of exogenous environmental factors into the body is the gastrointestinal tract. In fact, this is the first barrier to the penetration of these factors into the body. Concentrations of chemical elements in food, one way or another, can affect the hydrolytic and transport functions of the small intestine, which we observed in experiments with long-term consumption of solutions with an increased content of sodium chloride in rats.